Yarrow Cultivate Culture Value - Zahirian, Gul Ahmad (Journal of Natural Sciences – Kabul University, 2022)
Yarrow (Achillea millefolium) is a perennial plant from the Asteraceae family. Yarrow has seen historical use as in traditional medicine, often because of its astringent effects. Yarrow uses in cooking and medicinal include the following, flowers, leaves and stems. Leaves can be consumed raw or cooked. Common yarrow prefers sunny locations on thin, sandy soils. Best grown has in lean, dry to medium, well-drained sandy loams in full sun. Plants do well in average garden soils and tolerate poor soils as long as drainage is good. Plants also tolerate hot, humid summers and drought. You’ll see yarrow along roadsides, in fields, waste areas, canyon bottoms, grasslands and open forests and even on lawns. Flower heads are arranged in large, compact clusters at the top of the stem. Each cluster consists of 1 or more flower heads.